2013
DOI: 10.1016/j.nicl.2013.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid imaging in cognitively normal individuals, at-risk populations and preclinical Alzheimer's disease

Abstract: Recent developments of PET amyloid ligands have made it possible to visualize the presence of Aβ deposition in the brain of living participants and to assess the consequences especially in individuals with no objective sign of cognitive deficits. The present review will focus on amyloid imaging in cognitively normal elderly, asymptomatic at-risk populations, and individuals with subjective cognitive decline. It will cover the prevalence of amyloid-positive cases amongst cognitively normal elderly, the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
315
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(335 citation statements)
references
References 116 publications
15
315
2
3
Order By: Relevance
“…Similar to our colocalized PiB/MRI analyses, although only the parahippocampal gyrus neared statistical significance in our analysis of the potential Ab-induced acceleration of agerelated cortical thinning, there was a general tendency for increased Ab to be associated with faster age-related cortical thinning across the other ROIs examined. This supports the notion that even ostensibly mild Ab aggregation might not be innocuous, perhaps becoming more pernicious with the passage of time [47].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Similar to our colocalized PiB/MRI analyses, although only the parahippocampal gyrus neared statistical significance in our analysis of the potential Ab-induced acceleration of agerelated cortical thinning, there was a general tendency for increased Ab to be associated with faster age-related cortical thinning across the other ROIs examined. This supports the notion that even ostensibly mild Ab aggregation might not be innocuous, perhaps becoming more pernicious with the passage of time [47].…”
Section: Discussionsupporting
confidence: 78%
“…A meta-analysis of studies investigating Ab-cognition effects in CN individuals [49] suggested that although there is a modest association between amyloid accumulation and cognition, effect sizes in areas other than episodic memory and global cognition are small. Chetelat and colleagues [47] suggested that the variations in the observed effect of Ab on cognition may be due to differences in the underlying characteristics of the study samples, especially in age and APOE ε4 status. In the present study, we found that, despite the apparent Ab-induced degeneration of the entorhinal cortex and amygdala-two structures critical to episodic memory-there were no statistically significant main effect of Ab on memory or other cognitive functions, although the Ab1 group consistently exhibited lower cognitive test scores than the Ab2 group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the biphasic distribution in the HAMCs (Figure 1), using a more conservative wcDVR cutoff such as 1.5 35 would further strengthen, rather than weaken, this observation, since using this cutoff would result in 3/9 HAMCs versus 2/11 CAA patients being PiB þ . As reviewed recently, 18,36 20% to 40% of healthy elderly 460 years of age (and up to 50% above 80) have a significant amyloid burden on PET imaging, despite normal general cognition. 37 Our prevalence of 44% is therefore high but consistent with these ranges.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some patients with 'typical' signs and symptoms of AD show negative scans. So for the time being a positive amyloid scan must be considered in the full clinical picture of a patient, on the other hand, a negative amyloid scan indicates that the likelihood of cognitive impairment due to AD might be low, nevertheless, further data on sensitivity and specificity are needed [135][136][137][138].…”
Section: Clinical Trials For Ad: Regulatory Viewpoints and Requirementsmentioning
confidence: 99%